Modeling Secondary Health Conditions in Adults Aging With Physical Disability. (April 2014) - Molton, Ivan R.; Terrill, Alexandra L.; Smith, Amanda E.; Yorkston, Kathryn M.; Alschuler, Kevin N.; Ehde, Dawn M.; Jensen, Mark P.
Objectives: To test a conceptual model of secondary health conditions, age, and function in persons aging with long-term physical disabilities.Methods: Surveys were collected from 1, 862 adults with spinal cord injury, neuromuscular disease, multiple sclerosis, or post-polio syndrome. Structural equation modeling was used to build a model describing relationships among physical and psychosocial secondary health conditions, pain, functional impairments, chronic medical conditions, and age.Results: In total, 12 individual symptom or function domains (latent factors) were identified, grouped into 5 broader factors. Increasing age was associated with greater rates of physical and health problems and poorer function, and showed curvilinear relationships with pain and psychosocial difficulties.Discussion: These data support a biopsychosocial model of secondary health conditions in adults aging with physical disability and suggest a five-factor approach for conceptualizing secondary conditions and their impact. Results also emphasize the importance of age in symptom severity and impact.